2020
DOI: 10.3390/nu12092578
|View full text |Cite
|
Sign up to set email alerts
|

Is the Sustainable Choice a Healthy Choice?—Water Footprint Consequence of Changing Dietary Patterns

Abstract: It is evident that the modification of dietary patterns is a necessary precondition of disease prevention and health improvement. Changing nutritional habits also has deep-rooted consequences on the environmental burden. The majority of similar previous studies have analyzed the change in greenhouse gas emissions against theoretical modifications in current food consumption. The analysis on the effect of diet on the water footprint is also gaining in importance, since water supply is a critical global issue. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
(125 reference statements)
3
14
0
Order By: Relevance
“…There is no clear agreement on the association of healthiness and the environmental impact of diets in general [9,15,[51][52][53][54], but the synergy between a healthier diet and a lower dietary footprint does exist. This has also proven true for the dietary water footprint by this and numerous other studies analyzing the shift between the observed and healthier diets [9,[18][19][20]35,41,[55][56][57]. However, this association is neither linear nor general, which is also well presented in this study.…”
Section: Possible Reduction Of the Dietary Water Footprint By Changin...supporting
confidence: 72%
“…There is no clear agreement on the association of healthiness and the environmental impact of diets in general [9,15,[51][52][53][54], but the synergy between a healthier diet and a lower dietary footprint does exist. This has also proven true for the dietary water footprint by this and numerous other studies analyzing the shift between the observed and healthier diets [9,[18][19][20]35,41,[55][56][57]. However, this association is neither linear nor general, which is also well presented in this study.…”
Section: Possible Reduction Of the Dietary Water Footprint By Changin...supporting
confidence: 72%
“…According to Bickart and Ruth, "environmental concern can be defining consumers' appearance of problems about the importance of the environment for the benefits in the welfare of the nation [67]". Customers who are worried about environmental issues are positive about green products and highly motivated to buy eco-friendly products to maintain a good healthy lifestyle [68][69][70]. Earlier scholars found in their study that environmental concern affects the consumer's purchasing decision process, especially for green products [17,23,61,71,72].…”
Section: Environmental Concernmentioning
confidence: 99%
“…Dietary WF assessments have been conducted at global level [48,49], at national level with global coverage [50,51], continental or regional scale [45,52], individual country level [53][54][55][56][57][58][59][60][61][62][63], river basin level [64], provincial level [61], city level up to inner-city/borough level [34,[65][66][67][68][69][70][71] and for specific socioeconomic groups [65,[72][73][74]. Harris et al [33] also provide a selected overview of relevant studies.…”
Section: Geographical Coverage Data Used and Modelling Approachesmentioning
confidence: 99%